SPE Reservoir Simulation Symposium 2015
DOI: 10.2118/173221-ms
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Extrapolation of Black and Volatile Oil Fluid Properties Above Original Saturation Pressure for Tight and Conventional Reservoirs

Abstract: Black-oil fluid properties are determined by lab measurements or can be calculated through flash calculations of the reservoir fluid. Allowing for a variable bubble-point pressure in black-or volatile-oil models requires a table of fluid properties be extended above the original bubble-point. Reservoir simulation accuracy, however, may be affected by discontinuities in the input data and poor predictions of extrapolated fluid properties. Common practice is to add surface gas to the original oil in the lab and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Theoretical work has shown that the bubble-point pressure decreases due to the reduction of pore radius6789. The further the reservoir condition is from the critical point, the larger the reduction of bubble-point pressure.…”
mentioning
confidence: 99%
“…Theoretical work has shown that the bubble-point pressure decreases due to the reduction of pore radius6789. The further the reservoir condition is from the critical point, the larger the reduction of bubble-point pressure.…”
mentioning
confidence: 99%